Simple shear in 3D DEM polyhedral particles and in a simplified 2D continuum model - Langston, Paul; Ai, Jun; Yu, Hai-Sui (Springer Verlag, 2013)
We develop a discrete element model (DEM) simulation of mixed regular rounded polyhedra and spheres in simple shear with walls and periodic boundaries in 3-dimensions. The results show reasonably realistic behaviour developing shear and dilation or compaction depending on whether the initial state is dense or loose. Similarly non-coaxiality of principal stress direction and strain rate direction are shown. Polyhedra show more general realistic behaviour than spheres but take significantly longer to run. Particle forces include normal elastic, damping, and tangential friction and rolling friction. No cohesion or interstitial fluid is modelled. A separate simplified dynamic implicit finite difference Eulerian continuum model is developed and its parameters are used to fit the DEM results. This uses mass and momentum balances, a non-linear constitutive model and Mohr–Coulomb failure criterion. It runs in 2D with periodic boundaries effectively making it pseudo-1D. The model can reproduce the general trend of the DEM results and is a good basis for further development and understanding the physics.